Maternal pre-pregnancy body mass index, smoking in pregnancy, and alcohol intake in pregnancy in relation to pubertal timing in the children - Brix, Nis (BMC Pediatr, 2019)
BACKGROUND: Earlier pubertal timing has been observed in many countries. We aimed to explore if prenatal exposure to maternal obesity, smoking, and alcohol intake was associated with timing of puberty by use of a novel marker of pubertal timing: ‘the height difference in standard deviations’ (HD:SDS). METHODS: HD:SDS is the difference between pubertal height in standard deviations and adult height in standard deviations, and it correlates well with age at peak height velocity. Pubertal height was measured by health care professionals at approximately 13 years in boys and 11 years in girls, and the children’s adult height was predicted from parental height reported by the mothers during pregnancy. Information on HD:SDS was available for 42,849 of 56,641 eligible boys and girls from the Danish National Birth Cohort born 2000–2003. In a subsample, HD:SDS was validated against age at the following self-reported pubertal milestones: Tanner stages, menarche, first ejaculation, voice break, acne, and axillary hair. Prenatal exposures were reported by mothers during pregnancy. RESULTS: HD:SDS correlated moderately with the pubertal milestones considered (correlation coefficients: − 0.20 to − 0.53). With normal weight (body mass index (BMI): 18.5–24.9 kg/m(2)) as the reference, maternal pre-pregnancy obesity (BMI: 30.0+ kg/m(2)) was associated with earlier pubertal timing: 0.23 (95% confidence interval (CI): 0.18, 0.28) higher HD:SDS in boys and 0.19 (95% CI, 0.14, 0.24) higher HD:SDS in girls. Maternal smoking was not associated with pubertal timing. Compared to alcohol abstainers, maternal intake of > 3 units of alcohol weekly was associated with later puberty in boys only: 0.14 (95% CI, 0.05, 0.24) lower HD:SDS. CONCLUSION: As correlations between HD:SDS and the considered pubertal milestones were comparable to those reported in the literature between age a peak height velocity and the considered pubertal milestones, the validity of HD:SDS seems acceptable. Maternal pre-pregnancy obesity was associated with earlier pubertal timing in both sexes, and maternal alcohol intake during pregnancy was associated with later pubertal timing in boys. Maternal smoking has been linked to earlier timing of puberty, but this was not replicated in our setting using HD:SDS as a marker of pubertal timing.